-2(6y-6)-y=-3(y-3)

Simple and best practice solution for -2(6y-6)-y=-3(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6y-6)-y=-3(y-3) equation:


Simplifying
-2(6y + -6) + -1y = -3(y + -3)

Reorder the terms:
-2(-6 + 6y) + -1y = -3(y + -3)
(-6 * -2 + 6y * -2) + -1y = -3(y + -3)
(12 + -12y) + -1y = -3(y + -3)

Combine like terms: -12y + -1y = -13y
12 + -13y = -3(y + -3)

Reorder the terms:
12 + -13y = -3(-3 + y)
12 + -13y = (-3 * -3 + y * -3)
12 + -13y = (9 + -3y)

Solving
12 + -13y = 9 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
12 + -13y + 3y = 9 + -3y + 3y

Combine like terms: -13y + 3y = -10y
12 + -10y = 9 + -3y + 3y

Combine like terms: -3y + 3y = 0
12 + -10y = 9 + 0
12 + -10y = 9

Add '-12' to each side of the equation.
12 + -12 + -10y = 9 + -12

Combine like terms: 12 + -12 = 0
0 + -10y = 9 + -12
-10y = 9 + -12

Combine like terms: 9 + -12 = -3
-10y = -3

Divide each side by '-10'.
y = 0.3

Simplifying
y = 0.3

See similar equations:

| 4(x+6)-2(5-7x)= | | 11-5x=-7x+17 | | 4x-2y-12=0 | | 8x+6=abc | | -6=1-2n+5 | | (5n)*(5n)= | | 8-x=(x+6)(x+6) | | -b^5+2b^4-8= | | r+1.6=2r+1 | | 8428x-4116=98(86x-42) | | 7(9-3a)+13=13 | | 12x-6-8x=2x+2x-6 | | 30-6m-8=24 | | 180+0.15x=x-289.50 | | (5n)x(5n)= | | 4x+30=51 | | x(x+5)-2(x-4)=12 | | r+16=2r+1 | | 4x+6=x-2y | | 4x+x=51 | | X-2(2x-7)=2(x-8) | | 186x=1132-16 | | abs(3x+4)=-3 | | w-(-8)=47 | | -4.8=3.2 | | 25+10(12-x)=5(3x-7) | | 41x-12(x-4)= | | 20=20*log(x) | | 7x+17x-7=6(4x+10) | | x^2+5x-2x=12-8 | | 0.25x+25=0.50x+15 | | -3.268=0.3k-0.7 |

Equations solver categories